A network pharmacology-based study on the quality control markers of antithrombotic herbs: Using Salvia miltiorrhiza - Ligusticum chuanxiong as an example. (28th June 2022) - Zhang, Dai-Yan; Peng, Ruo-Qian; Wang, Xu; Zuo, Hua-Li; Lyu, Li-Yang; Yang, Feng-Qing; Hu, Yuan-Jia
Abstract: Ethnopharmacological relevance: Salvia miltiorrhiza (Danshen, DS), the dried root and rhizome of Salvia miltiorrhiza Bunge and Ligusticum chuanxiong (Chuanxiong, CX), the dried rhizomes of Ligusticum striatum DC are effective in invigorating blood circulation and eliminating stasis which is highly related with cardiovascular disease (CVD). Aim of study: The identification of activity-based chemical markers is very important, but the complex mechanism of "multi-component, multi-target, and multi-effect" within traditional Chinese medicine (TCM) poses a great challenge to this work. In this study, we combined network pharmacological prediction with experimental validation of the DS and CX to explore an effective method for discovering quality control (QC) of antithrombotic herbs by clarifying the intermediate layer "module/cluster" between the whole complex system and a single component. Materials and methods: Based on structural similarity analysis of compound and the thrombosis network published before, we firstly modularized two layers called chemical cluster (CC) network and functional module (FM) network respectively and linked them into one bilayer modularized compound target (BMCT) network. "Two-step" calculation was applied on identifying the significant compounds as the potential QC markers from CC. The in vitro inhibitory activity of selected QC marker compounds on thrombin was evaluated to partially verify their pharmacological activities. HPLC was used to determine contents. Results: According to the network-based analysis, nine compounds with great importance in the BMCT network were identified as QC markers of DS-CX, including tanshinone I, tanshinone IIA, cryptotanshinone, salvianolic acid B, ferulic acid, salvianolic acid A, rosmarinic acid, chlorogenic acid, and coniferyl ferulate. Enzyme inhibitory test partially verified the activity of tanshinone I and tanshinone IIA. Chemical profiling indicated that the nine marker compounds are the main components in the herbal pair. Conclusions: This study identified activity-based QC markers of DS-CX herbal pair and provided a new methodology that can be used in the QC of other herbs, herbal pairs, or formulas. Graphical abstract: Image 1